Size-dependent effective behaviors of multiferroic fibrous composites with interface stress. (February 2017) - Kuo, Hsin-Yi; Wang, Kai-Hong
Abstract: The objective of this work is to study the size-dependent effective behaviors of multiferroic fibrous composites with interface stress subjected to generalized in-plane deformation and out-of-plane electromagnetic fields. Using the complex variable approach together with several micromechanical models, closed-form expressions of the effective moduli are obtained. In contrast to the composite with perfect bonding, the effective property formulations show the dependence on the size of the fibers. The derived solutions are applied to several examples to demonstrate the effect of interface stress, and to examine the results among different micromechanical models. Numerical results show that while most of the effective moduli increase as the radius of the fiber decreases, the magnetoelectric voltage coefficient, the figure of merit of the multiferroic material, decreases. Further, when considering the effective transverse shear modulus of composite with interface stress, a higher order approximation is required for the equivalency between an interphase and an imperfect interface if the interphase is not sufficiently thin or is very stiff.